Evaluation of the masticatory biomechanical function in Down syndrome and its Influence on sleep disorders, body adiposity and salivary parameters - Gomes, Mônica Fernandes [UNESP]; Giannasi, Lilian Chrystiane [UNESP]; Fillietaz-Bacigalupo, Elaine [UNESP]; de Mancilha, Gabriela Pinto [UNESP]; de Carvalho Silva, Gabriela Raine [UNESP]; Soviero, Laura Dias [UNESP]; da Silva, Gabriella Yasmin Santos [UNESP]; Nazario, Letícia de Miguel [UNESP]; Dutra, Marignês Theotonio dos Santos [UNESP]; Silvestre, Pedro Ribeiro; de Oliveira, Luis Vicente Franco; Nacif, Sérgio Roberto; et al. (Wiley, 2020)
Objective: To evaluate the phenotypic features of the masticatory biomechanics in atypical subjects with Down syndrome (DS). Its influence was analysed on sleep disorders, body adiposity and its risks, and some physicochemical properties of saliva. Methods: Seventy subjects were enrolled to assess masticatory biomechanical function and divided into two groups: DS and control groups. Electrical activities of the masseter and temporal muscles (at rest and in maximum voluntary clench-MVC), maximum bite force-MBF and maximum mouth opening-MMO were investigated. Among the atypical subjects, just 24 participants underwent the anthropometry, the polysomnography II and the saliva testing (salivary flow rate-SFR, buffer capacity-BC and salivary cortisol levels, morning/SC-AM and night/SC-PM). Results: MVC and MBF values showed high statistical significance in the control group (P <.001) than in the DS group of 35. MMO values were slightly increased in the DS group in relation to the control group. Overweight and obesity were found in both genders. Atypical women showed higher risk to develop cardiovascular-metabolic diseases than in atypical men. OSA severe was 20% for atypical women and 42.8% for atypical men, whereas snoring index was present in all genders. SFR was reduced in 100% of atypical subjects (hyposalivation in 10% women and 28.5% men). Furthermore, 100% BC, 66.6% SC-AM and 91.6% SC-PM showed normal patterns. Conclusion: Masseter and temporal muscle hypotonia was found in all atypical subjects with DS. This muscle dysfunction strongly was related to overweight/obesity, risks for development of cardiovascular/metabolic diseases, OSA severity, successive snoring episodes and salivary flow reduction in DS.
Keywords: adiposity; Down Syndrome; masticatory muscles; muscle hypotonia; saliva; sleep disorders